Alien clay - Tchaikovsky, Adrian, 1972- (Orbit, 2024)
Exiled for political activism to a labor camp on the distant world of Kiln, Professor Arton Daghdev battles to survive daily camp life as well as interactions with Kiln's alien life, not knowing that Kiln itself holds a secret that may become his salvation.